A bibliometric and visual analysis of low carbohydrate diet - Lu, Gang; Huang, Xin; Lin, Chun; Zou, Lijuan; Pan, Huashan (Frontiers in Nutrition, 2023)
Introduction Numerous studies have confirmed the effects of low carbohydrate diet (LChD) on metabolism and chronic diseases. However, there were no bibliometric studies on LChD. This study was conducted through a bibliometric analysis to investigate the current status, hotspots and frontiers trends. Methods We searched all research publications related to LChD from 2002 to 2021 on the Web of Scientific Core Collection (WoSCC). CiteSpace and VOSviewer software was used to analyze countries/regions, institutions, journals, authors, references, and keywords. Results A total of 6938 papers were included, with an increasing trend of annual publication. LChD categories mainly included nutrition, endocrinology, and neurosciences which reflected the interdisciplinary characteristics. USA was with the largest number and the world science center in LChD field. Universities were main research institutions and five of the top 10 institutions were from USA. Eric Heath Kossoff had 101 publications and ranked first. Nutrients was the leading journal. “A randomized trial of a low-carbohydrate diet for obesity” and “Obesity” were considered to be the most co-cited and cited reference respectively. The hotspots of LChD are four aspects, “ketogenic diet”, “metabolism disease”, “cardiovascular disease” and “cancer”. We summarized that “oxidative stress”, “gut microbiota”, and “inflammation factors” are becoming frontiers trends of LChD research in the future and deserve further study. Discussion Over the past 20 years research on LChD has gained great attention. To better explore LChD field, multilevel mechanism studies will be required in the future.